From Discovery to Impact: The Ideal Balance Between Exploratory and Applied Research in Engineering - Szu Kai, Lee; Baharudin, Mohamad Ezral; Saad, Mohd Sazli; Zakaria, Mohd Zakimi; Mohd Nor, Azuwir (Advanced and Sustainable Technologies (ASET), 2026)
This paper discusses the current trends in the continuous discussion of exploratory and applied research in the engineering context: the necessity of a balance between both. Exploratory research extends the boundaries of knowledge in a scientific context, whereas applied research provides a leap toward effective solutions based on that knowledge. The paper suggested that engineering researchers’ focus needed to be on applied research, which is the essence of all technology innovation, unless the exploratory research subject matter is still maturing. Each developing country can focus on an applied/supported effort to overcome an immediate community challenge, e.g., technologies for clean drinking water and renewable energy needs, whereas developed countries may continue an exploratory research line through applied research. Further, the paper proposed that scientists and engineers collaborate to mitigate research overlaps and efficiently apply discoveries to local challenges. Therefore, engineers can use existing knowledge and skills to create innovative technologies, improve the quality of life, and advance industrial development. All engineering applied research will provide a translationally appropriate balance as the core of both technological and societal sustainable growth. Applied research is the core of engineering growth.